The FarNet journey: Perceptions of Māori students engaged in secondary online learning - Carolyn Bennett; Michael K Barbour (Flexible Learning Association of New Zealand, 2012)
This case study investigated the perceptions of Māori students in the Virtual Learning Network (VLN) on what constituted effective strategies for engaging them in online learning. The four secondary and five area schools in the FarNet cluster have around 63 students accessing the VLN. Around 80% of students, known as e-students, from the FarNet cluster receiving their education through the VLN are of Māori descent. The delivery of online classes have historically included a one hour video conferencing (VC) class, supported by hard copy materials and resources provided by the e-teacher or an online learning environment called a Learning Management System (LMS). The model that is now starting to emerge is a hybrid model which combines weekly VC classes, an LMS, a range of Web 2.0 tools and face-to-face meetings between student and teacher. Data collection included online surveys, the semi-structured interviews and the observation of the online classrooms with 23 students from nine school participating in FarNet. The data identified delivery models and Web 2.0 tools to engage students and the need for further instruction in order for students to be well prepared to work in this new learning environment. The data also suggested there were a variety of delivery models that students experienced, most supported by the LMS. While students identified a range of Web 2.0 strategies currently used by their e-teachers, they suggested that more opportunities to collaborate, communicate and discuss with their fellow e-students both in and outside of the set class time would further engage them, leading to a more enjoyable experience. The importance of building good relationships in an online environment was discussed. Based on these findings, we recommend professional development for e-teachers on using these emerging tools and better preparation of e-students for working in an online learning environment.